Hushabye Lily - Freedman, Claire (London Little Tiger, 2003)
What's that quacking sound I can hear?" asks Lily. "Sorry" says a Golden-eyed Duck, and he sings the most beautiful duck lullaby he knows. But just as Lily is drifting off to sleep, she hears, "Tu-whit, tu-whoo!" Will the other animals ever be quiet so that Lily can get to sleep at last?
Keywords: Wakefulness -- Domestic animals